Participação do óxido nítrico no efeito hipotensivo e vasodilatador induzido pela fotobiomodulação utilizando laser de 660 nm - Buzinari, Tereza Cristina (2021)
Introduction: Photobiomodulation (PBM) is a non-invasive therapeutic modality used to treat several pathologies. Studies indicate that nitric oxide (NO) can be released from endogenous “stocks” by photolysis, favoring the biological effects of NO. Aim: Evaluate whether the application of red laser induces a decrease in blood pressure in spontaneously hypertensive rats (SHR) and whether this effect is dependent on the release of NO stock. Methods: Direct measurement (Basal, Sham and after FBM) of the hemodynamic parameters of hypertensive L-NAME and SHR rats was performed. Rats treated with L-NAME produce less NO and, consequently, less NO stock. A red laser (660 nm) was used; 80 mW; 56 seconds/point (6 points, abdominal region); 4.5 J; 63 J/cm2 per point. Normotensive and L-NAME rats were euthanized by decapitation, and the thoracic aorta was collected dissected for vascular reactivity study. Three laser applications were performed on the same aortic ring: first, after phenylephrine contraction; second, after endothelial integrity testing by acetylcholine; third, after incubation for 30 minutes with the NO donor DETA-NO, PBS or Hydroxicobalamin. The irradiation parameters for vascular reactivity were: red laser (660 nm); 100 mW; 56 seconds; 5.6J; 96 J/cm2. Endothelial cells (HUVEC) were treated with DETA-NO or CuSO4, with subsequent application of PBM (4.5 J) and addition of a selective fluorescent probe for NO (DAF-2 DA). Results: there was a decrease in systolic blood pressure in SHR (mean of 14 mmHg) and an increase in serum NO was detected by chemiluminescent reaction. Hypertensive L-NAME rats did not exhibit a decrease in blood pressure after PBM. PBM promoted vasodilation in the aorta isolated from normotensive rats, and less effect in the aorta of L-NAME rats and the addition of the NO donor, DETA-NO, promoted greater vasodilation by PBM in the aorta of L-NAME rats, however, the addition Hydroxycobalamin has abolished the vasodilator effect of PBM. In endothelial cells, an increase in NO, after PBM, was detected, however with the addition of CuSO4, which catalyzes the decomposition of NO stocks, there was no detection of NO after PBM. Conclusion: Our results demonstrate that, acutely, irradiation with red laser (660 nm) promotes a hypotensive and vasodilation effect through a mechanism that involves the mobilization of NO stock.